“Caring for the People”: ZuriaFM – An Islamic Radio Station in Asante, Ghana - Pontzen, Benedikt (Islamic Africa, 2018)
As an Islamic radio station, ZuriaFM stands as an exception in the heavily pentecostalized Ghanaian mediascape. In this essay, I locate this station in this mediascape and discuss the “Islamic sphere” it co-brings into being. Thereby, I complement the mainly Christian case studies of media, institutions, and actors in the Ghanaian public sphere with an Islamic one. ZuriaFM has emerged as a central platform for Muslims in the country, and has significantly (re-)shaped this “Islamic sphere” by introducing new styles of preaching, preacher figures, and opening topics for debate. In this sense, I by and large agree with the prevailing “transformation thesis” in the literature on “modern” media and “Islamic spheres” which stresses the fragmentation and liberalization of debates and authority. However, ZuriaFM could also be perceived as contributing to a unification of Islamic standards, which calls into question the one-sided stressing of fragmentation and liberalization of the “transformation thesis”.